Feira livre e reprodução camponesa no município de Irará/BA - Andréia Silva de Alcântara; Noeli Pertile (Confins)
In the historical process of formation of the municipality of Irará the former slaves reorganized their tactics of resistance in the countryside through different forms of access to land (squatter, partner, tenant, occupant and small owner) and this resulted in the existence of the present peasants. This is the context in which the peasantry was forged in the municipality of Irará, which allows for the continuation of the struggle and the preservation of the peasant way of life, expressed through traditional agriculture in the various manifestations of the know-how of this social group. Thus, much of the municipal agricultural production is marketed at the free fair of the municipality of Irará. The free fair is an oxygenator of the peasant economy. It is where the peasant carries on the exchange of commodities produced by him (of what he exceeds in his establishment) for money and other commodities essential for his subsistence. The free fair is also the space of relations of sociability, cultural manifestations and leisure. The free fair of the municipality of Irará presents a diversity of products, which originate, for the most part, from the rural communities of the municipality of Irará. The diversity of these products expresses the importance of peasant agriculture in supplying the local market. Consequently, the fair of the municipality of Irará is the space where the local economy moves, where the work of the peasant materializes in the currency of purchase and exchange. It is the space that guarantees peasant reproduction and, at the same time, weaves the relations between the countryside and the city.